2005
DOI: 10.1007/s11661-005-0181-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of solidification conditions on the castability of nickel-base superalloy IN792

Abstract: The effect of withdrawal rate on hot tearing or solidification cracking during directional solidification (DS) was explored. High withdrawal rates were found to reduce the hot tearing tendency. There is a general refinement of the microstructure when the withdrawal rate is increased. First, the dendrite arm spacing appears smaller. Second, the columnar grain size is reduced. Third, the remaining liquid is finely dispersed and increasingly discontinuous. Finally, a more uniform distribution of strain is obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…In another investigation, 13 we found that solidification rate is able to affect the geometry and distribution of remaining liquid, although the volume fraction of the remaining liquid is independent of the solidification rate. The remaining liquid becomes more finely dispersed and increasingly discontinuous at a higher solidification rate because of the refinement of dendrites and columnar grains.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…In another investigation, 13 we found that solidification rate is able to affect the geometry and distribution of remaining liquid, although the volume fraction of the remaining liquid is independent of the solidification rate. The remaining liquid becomes more finely dispersed and increasingly discontinuous at a higher solidification rate because of the refinement of dendrites and columnar grains.…”
Section: Introductionmentioning
confidence: 76%
“…Therefore, dendrite arm spacing and columnar grain size were reduced simultaneously in the previous work 13 when the solidification rate was increased. As such, the effects of the dendrite arm spacing and columnar grain size on castability could not be studied separately.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Moreover in another study Zhang and Singer (2004a,b) obtained a crack free specimen with grain boundary misorientation angle less than 12 • . Zhou et al (2005) investigated the grain boundary characteristics and proved that the presence of an interdendritic eutectic phase supresses hot tearing. Zhou and Volek (2006) explored the effect of grain boundary (GB) fraction and showed higher GB fraction has a positive effect on lowering the hot tear tendency.…”
Section: Introductionmentioning
confidence: 99%